T1 relaxation time of ISMRM/NIST T1 phantom spheres at 7 T. (23rd November 2022) - Yen, Yi‐Fen; Stupic, Karl F.; Janicke, Michael T.; Greve, Douglas N.; Mareyam, Azma; Stockmann, Jason; Polimeni, Jonathan R.; van der Kouwe, Andre; Keenan, Kathryn E.
Abstract : T1 relaxation times of the 14 T1 phantom spheres that make up the standard International Society for Magnetic Resonance in Medicine (ISMRM)/National Institute of Standards and Technology (NIST) system phantom are reported at 7 T. T1 values of six of the 14 T1 spheres at 7 T (with T1 > 270 ms) have been reported previously, but, to the best of our knowledge, not all of the T1s of the 14 T1 spheres at 7 T have been reported before. Given the increasing number of 7‐T MRI systems in clinical settings and the increasing need for T1 phantoms that cover a wide range of T1 relaxation times to evaluate rapid T1 mapping techniques at 7 T, it is of high interest to obtain accurate T1 values for all the ISMRM/NIST T1 spheres at 7 T. In this work, T1 relaxation time was measured on a 7‐T MRI scanner using an inversion‐recovery spin‐echo pulse sequence and derived by curve fitting to a signal equation that exhibits insensitivity to B 1 + inhomogeneity. Day‐to‐day reproducibility was within 0.4% and differences between two different RF coils within 1.5%. T1s of a subset of the 14 spheres were also measured by NMR at 7 T for comparison, and the T1 results were consistent between the MRI and NMR measurements. T1 measurements performed at 3 T on the same 14 spheres using the same sequence and fitting method yielded good agreement (mean percentage difference of −0.4%) with the reference T1 values available from the NIST, reflecting the accuracy of the reported technique despite being without the standard phantom housing. We found that the T1 values of all 14 NiCl2 spheres are consistently lower at 7 T than at 3 T. Although our results were well reproduced, this study represents initial work to quantify the 7‐T T1 values of all 14 NIST T1 spheres outside of the standard housing and does not warrant reproducibility of the ISMRM/NIST system phantom as a whole. A future study to assess the T1 values of a version of the ISMRM/NIST system phantom that fits inside typical commercial coils at 7 T will be very helpful. Nonetheless, the details on our acquisition and curve‐fitting methods reported here allow the T1 measurements to be reproduced elsewhere. The T1 values of all 14 spheres reported here will be valuable for the development of quantitative MR fingerprinting and rapid T1 mapping for a large variety of research projects, not only in neuroimaging but also in body MRI, musculoskeletal MRI, and gadolinium contrast‐enhanced MRI, each of which is concerned with much shortened T1. Abstract : T1 relaxation times of the 14 NiCl2 spheres that made up the standard ISMRM/NIST system phantom are reported at 7 T for the first time, which may facilitate their use as reference values for rapid T1 mapping developments at 7 T.